MENTAL EDUCATION OF STUDENTS (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
The content of education in this articles is knowledge, skills, character, behavior, system. The goal of education is to form a well-rounded person, to increase interest in learning, and to widely promote the correct use of modern information flow.